'More than one red herring'? Heterogeneous effects of ageing on health care utilisation. (17th July 2020) - Costa‐Font, Joan; Vilaplana‐Prieto, Cristina
Abstract: We study the effect of ageing, defined as an extra year of life, on health care utilisation. We disentangle the direct effect of ageing, from other alternative explanations such as the presence of comorbidities and endogenous time to death (TTD) that are argued to absorb the effect of ageing (so‐called 'red herring' hypothesis). We exploit individual level end of life data from several European countries that record the use of medicine, outpatient and inpatient care and long‐term care. Consistently with the 'red herring hypothesis', we find that corrected TTD estimates are significantly different from uncorrected ones, and their effect size exceeds that of an extra year of life, which in turn is moderated by individual comorbidities. Corrected estimates suggest an overall attenuated effect of ageing, which does not influence outpatient care utilisation. These results suggest the presence of 'more than one red herring' depending on the type of health care examined.